Induction Motor Control Didactic Set-up Using Sensorless And Sliding Mode Dtc Strategy - Lazarini, Marcos Vinicius; Filho, Ernesto Ruppert (Eletrônica de Potência, 2008)
A three-phase induction motor direct torque control laboratory set-up for simulation and experimental activities is presented in this paper. It includes sliding-mode controllers and uses a sensorless method to estimate rotor speed. The objective of this setup is to present to the students a simulation tool based on Matlab SimPowerSystems toolbox with the possibility to check simulation results against a DSP based experimental system. The set-up provides to the electrical engineering students an excellent learning tool for nonlinear control studies using as example the variable speed three-phase induction motor control. Linear control systems are extensively studied in electrical and computer engineering theoretical and experimental sessions while non-linear control systems aren’t.